Design and Development of a Microstrip Sensor for Measurement of Moisture Content in Rice Grains - Jafari, Fariba (2007)
A Microstrip moisture sensor is developed based on microwave attenuation and is used for measuring moisture content of rice grains. This sensor is suitable for a broad range of moisture content ranging from 0% to 40 % (wet basis). It was fabricated using RT-Duriod with dielectric properties of 2.2-j0.002 as the substrate, with operating frequency at 9.0 GHz. In this technique only the small part of sample is needed to contact with the microstrip line, therefore the measurement can be done with more accuracy and in a shorter time. Theoretical analysis based on quasi-transverse electromagnetic mode (TEM mode) in four layered microstrip is carried out to evaluate design parameters such as microstrip characteristic impedance, effective dielectric constant, length and thickness due to the sensitivity of the sensor. The analysis of the complex electromagnetic waves in this system is presented using signal flow graphs and solved by Mason's non-touching loops rules. To this end Visual Fortran programs is written and documented to evaluate all the design parameters needed and to estimate the microstrip patterns. In the other part of this study, investigation was made to find the relation between the dielectric properties and moisture content of rice grains. The dielectric mixture theory has been derived to solve the problem of non homogenous medium. In the purpose of verifying the mixture theory the theoretical results has been compared with the empirical results. It was found that the dielectric properties of dried rice samples were in the range of 1.20 to 1.88 for ε′ and 0.065 to 0.23 for ε″ and even can increased up to 30-j18 in maximum moisture content, respectively. A close and good agreement to theoretical expectation values is found. A computer program EMIX is written to predict the dielectric properties of wet basis rice grain by knowing the values of physical properties for dry basis. In this study, analyzes of the sensor and various type of the rice grain samples with the effect of density and temperature of rice grains to the total attenuation of the sensor has been studied and the predicted results are compared with experimental results. The effect of air inside the medium and the compactness of the material under the test has been studied and the errors of ± 0.16 dB has been calculated for the measured reflected attenuation of the sensor. The micrsotrip sensor was tested on five types of rice grains in the range of 1% to 40% moisture content. The sensor has predicted moisture contents with standard error of ±0.22 dB and accuracy of 1.5% MC wet basis compared to standard oven drying method. Moisture contents of rice grain samples were found in the range of 11 to 12.5% at room temperature (25°C). A new proposed moisture sensor which can measure the moisture content of grains contained in a sack manner has been given. The slim and sharp geometry of the sensor enable it to measure the mean volumetric values of moisture content of rice since it penetrates deep into the sack. Therefore, this method can be so useful in industry for moisture content measurement of rice grains and even some other grains like wheat, corn barley and so on, to determine the proper time of harvest, safe storage and quality control of grains.